Inactivation of a Pleurotus ostreatus versatile peroxidase‐encoding gene (mnp2) results in reduced lignin degradation. (10th October 2013) - Salame, Tomer M.; Knop, Doriv; Levinson, Dana; Mabjeesh, Sameer J.; Yarden, Oded; Hadar, Yitzhak
Summary Lignin biodegradation by white‐rot fungi is pivotal to the earth's carbon cycle. Manganese peroxidases (MnPs), the most common extracellular ligninolytic peroxidases produced by white‐rot fungi, are considered key in ligninolysis. Pleurotus ostreatus, the oyster mushroom, is a preferential lignin degrader occupying niches rich in lignocellulose such as decaying trees. Here, we provide direct, genetically based proof for the functional significance of MnP to P. ostreatus ligninolytic capacity under conditions mimicking its natural habitat. When grown on a natural lignocellulosic substrate of cotton stalks under solid‐state culture conditions, gene and isoenzyme expression profiles of its short MnP and versatile peroxidase (VP)‐encoding gene family revealed that mnp2 was predominately expressed. mnp2, encoding the versatile short MnP isoenzyme 2 was disrupted. Inactivation of mnp2 resulted in three interrelated phenotypes, relative to the wild‐type strain: (i) reduction of 14% and 36% in lignin mineralization of stalks non‐amended and amended with Mn2+, respectively; (ii) marked reduction of the bioconverted lignocellulose sensitivity to subsequent bacterial hydrolyses; and (iii) decrease in fungal respiration rate. These results may serve as the basis to clarify the roles of the various types of fungal MnPs and VPs in their contribution to white‐rot decay of wood and lignocellulose in various ecosystems.